High-yield, high-conductive graphene/nanocellulose hybrids prepared by Co-exfoliation of low-oxidized expanded graphite and microfibrillated cellulose. (15th November 2021) - Liu, Ke; Hu, Jie; Kong, Zhengqing; Hu, Jiawei; Tian, Zhishuai; Hou, Jiarui; Qin, Jinli; Liu, Chengshun; Liang, Shuai; Wu, Haipeng; Zhang, Jianming; Zong, Lu; et al.
Abstract: Nowadays, high performance and functional low-dimensional nanomaterials have been targeted in modern sustainable energy science for diverse potential applications. However, broad applications of emerging nanomaterials such as graphene and biomass nanofillers have suffered from low preparation efficiency, low quality of products, unstable dispersion in matrix. In this study, a 100% yield of low-oxidized graphene/nanocellulose hybrids (LGENC) was prepared by one-pot ball milling. Low-oxidized expanded graphite (LOEG) and microfibrillated cellulose (MFC) were used as precursors for fabricating LGENC by the co-exfoliation strategy. That is, exfoliation of LOEG, nanofibrillation of MFC and their hybridization were simultaneously realized under the shear and collision of balls milling. The concentration of LGENC suspension can be concentrated to 50 mg/mL, which has great potential for 3D printing. A series of characterization identified the hybridization of low-oxidized graphene (LGE) and nanocellulose via hydrophobic and hydrogen bond interaction, and confirmed that the LGE has fewer oxygen functional groups and more complete structure than graphene oxide. Benefiting from the intact structure, the conductivity of LGENC can reach up to ~5800 S/m. In addition, the as-prepared LGENC showed significant potential in reinforcing rubber latex. In general, this study proposes a high-efficiency preparation method for graphene/cellulose hybrid materials with extraordinary properties. Graphical abstract: Image 1 Highlights: Co-exfoliation of low-oxidized expanded graphite and microfibrillated cellulose is a simple and efficient way to prepare hybrid nanomaterials. The concentration of as-prepared LGENC dispersion is as high as 13 mg/mL, which can be further concentrated to 50 mg/mL. The conductivity of as-prepared LGENC films exhibits obvious anisotropy, and the in-plane conductivity can reach up to ~5800 S/m. The as-prepared LGENC demonstrated significant reinforcing ability for carbonylated nitrile butadiene rubber.